EFFECTIVE METHODS OF FORMING STUDENTS' CRITICAL THINKING COMPETENCE (Scientific journal of the Fergana State University, 2025)
This article analyzes the theoretical and practical foundations of developing critical thinking competence in higher education students. The concept of critical thinking, its essence, role in the higher education system and its place in the modern educational process are revealed. Also, innovative pedagogical methods, educational technologies and didactic tools that serve to form critical thinking are considered. The article may be of practical importance for educators, researchers and specialists who aim to use innovative methods aimed at forming critical thinking in the educational process.